A combined goal programming – AHP approach supported with TOPSIS for maintenance strategy selection in hydroelectric power plants. (October 2017) - Özcan, Evren Can; Ünlüsoy, Sultan; Eren, Tamer
Abstract: Sustainable energy supply defined as uninterrupted, reliable, efficient, economic and environmentally friendly electricity generation is the main goal of power plants. Carrying out the proper maintenance processes has critical importance in terms of prolonging the effective operational lifetime of power plants and thus improving the sustainable power generation of the system. Since it serves for such an important purpose, maintenance is a crucial process that must be managed and selection of the most appropriate maintenance strategy is the first and unignorably stage of maintenance management in power plants as in other manufacturing facilities. Within this scope, this study focuses on the maintenance strategy selection problem in hydroelectric power plants have great importance for world and Turkey energy mix. As hydroelectric power plants comprise thousands of equipment with different characteristics, nine equipment which have similar effects and the most important ones for power plant are determined by The Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) under nine evaluation criteria weighted by the Analytic Hierarchy Process (AHP) for a big scale hydroelectric power plant in Turkey. Maintenance strategy combinations are obtained for each selected equipment via proposed goal programming (GP) model which uses the criteria weights and alternative priorities calculated with AHP and reflects the realities of power plant. Finally, it is determined that there is an improvement about 77% in downtimes arise from carrying out the improper maintenance strategy on selected critical equipment compared to the period when the model is not used.